Impact of household practices on the nutritional profile of milk - Sanjivan Bahman; Nidhi Yadav; Ajay Kumar; Sanjeev Ganguly; Vivek Garg; Satwinder S Marwaha (Wolters Kluwer Medknow Publications, 2012)
Background: It is a common practice to process milk before consumption. Processing generally involves boiling, addition of sugar and/or condiments, dilution with water, etc. The boiled milk is stored for subsequent use either at room temperature or under refrigerated conditions. Objective: The purpose of this study was to see the effect of household practices on the nutritional profile of milk. Materials and Methods: Different types of pasteurized milk samples: standardized, double toned, full cream, and unpasteurized milk were analyzed. The effect of household practices on the nutritional profile of all these milk samples was studied using National/International methods. Results: Boiling of milk increased the concentration of most of the components and minerals except for vitamins A, B 3 , B 5 , and B 12 where the decrease observed was 21%, 13%, 3%, and 21%, respectively. Addition of water decreased the concentration of minerals and vitamins. Addition of sugar increased the energy and condiments increased total solids, carbohydrate and minerals content but led to a decrease in the vitamin content. Storage of milk led to a decrease in total solids by 19% and vitamins A, B 3 , B 5 , and B 12 by 26%, 17-19%, 23%, and 18-26%, respectively. The pH was not influenced by any of the household practices. Conclusion: Every step during household practices in the handling of milk reduces its nutritional profile and significantly affects the quality. Vitamins play a very important role in health and loss during household processing becomes an interesting attribute that requires further research in detail.